Sheep and goats tick’s infestation in Wasit’s districts: Raad Hammodi Hasson 1 and Haleem Hamza Al-Zubaidi 2 - Hasson, Raad Hammodi (The Iraqi Journal of Veterinary Medicine, 2012)
The study was conducted in 4 districts regions in Wasit province during May – August 2010 to investigate the percentage of sheep and goat infestation ; out of 366 animals , 69 (18.85 %) were infested with total general tick mean 2.15 ; infested sheep were more prevalent 79.71% than goats 20.28% ; Highest no. of infestation were found in August 49.27% and June 24.63% . Two species of ticks , Rhipicephalus turanicus 94% on both sheep and goats , while Hyalomma anatolicum anatolicum only on sheep 6% were recorded. According to species of animal, sheep in azizia shows highest infestation in august (34.78%) followed by Suwara in june (14.49%) ; and for goat in azizia shows the highest infestation in may (7.24%) . There is significant difference between monthly infested sheep and goats p ≤ 0.028 .There is significant difference between districts containing infested sheep and goats p ≤ 0.000. There is no significant difference between infested sheep and goats p ≥ 0.12. Given data might be aid in epidemiology of ticks and minimize public and veterinary infections.